Digitalisasi Manajemen Data Alokon dengan Metode Agile pada Sudin PPAPP Jakarta Timur - Andriansah, Andriansah; Faadilah, Hafif; Santoso, Muhammad; Yaldi, Yaldi (JURNAL TEKNIK INFORMATIKA, 2025)
The rapid advancement of information technology has prompted government agencies to adopt digital systems for more effective data management. The East Jakarta Office of Women Empowerment, Child Protection, and Population Control (Sudin PPAPP) faces significant challenges in managing contraceptive supply data, which is still handled manually. This manual process often leads to inconsistent records, delayed reporting, and inefficiencies in data handling. This study aims to design and develop a web-based application to facilitate digital and real-time tracking, recording, and reporting of contraceptive tools and supplies. The software development follows the Agile methodology, allowing iterative development focused on user needs and feedback. The system includes features such as stock monitoring, distribution history, and automated PDF report generation. The results demonstrate that the application enhances data accuracy, streamlines workflow, and improves the overall service of the Family Planning program. This digital initiative is expected to serve as an initial step toward a more modern and integrated data management system